The respiratory health of swimmers - Bougault, V.l; Turmel, J.; Levesque, B.; Boulet, L. P. (Sports Medicine, 2009)
Regular physical activity is recognized as an effective health promotion measure. Among various activities, swimming is preferred by a large portion of the population. Although swimming is generally beneficial to a person's overall health, recent data suggest that it may also sometimes have detrimental effects on the respiratory system. Chemicals resulting from the interaction between chlorine and organic matter may be irritating to the respiratory tract and induce upper and lower respiratory symptoms, particularly in children, lifeguards and high-level swimmers. The prevalence of atopy, rhinitis, asthma and airway hyper-responsiveness is increased in elite swimmers compared with the general population. This may be related to the airway epithelial damage and increased nasal and lung permeability caused by the exposure to chlorine subproducts in indoor swimming pools, in association with airway inflammatory and remodelling processes. Currently, the recommended management of swimmers' respiratory disorders is similar to that of the general population, apart from the specific rules for the use of medications in elite athletes. Further studies are needed to better understand the mechanisms related to the development or worsening of respiratory disorders in recreational or competitive swimmers, to determine how we can optimize treatment and possibly help prevent the development of asthma.